SYSTEM PURCHASE / RESERVATION OF GOODS IN A-NET COMPUTER PROGRAMMING LANGUAGE USING MICROSOFT VISUAL BASIC 6.0 - Mohammad Dion Hartantyo; Fitri Sjafrina, SKom, MMSI (Jurnal Sistem Informasi, 2006)
System purchase / ordering of goods on the A-Net Computer consists of a purchase of data processing applications, as well as data of employees, suppliers, and goods. The application also provides information support to management functions in decision making.By using this application, is expected to assist parties interested in the trading business in obtaining the information they need, in addition to assisting also in the process of transactions that occur.